The correspondence between the Vatican and the Eastern Church of Levant in the last decade of the seventeenth century - Hasan, Samee (Études sur la Région Méditerranéenne, 2022)
The article aims at elaborating facts in the last decades of the seventeenth century depending on three correspondences between the Pope of the Vatican with two heads of the Christian Community in the East. The first manuscript is written in Syriac by the Patriarch of the Chaldean Church, announcing his doctrine to the Pope. The other two are written in Arabic by the Metropolitan of the East or the Syriac Catholic Metropolitan, a branch from the Syrian Orthodox church emphasizing on his credibility and loyalty, asking the Pope for his blessings and educational materials. On the other side, the manuscripts illustrate the success of the missionary expedition in its mission in the Levant during this time.